Pengembangan Media Pembelajaran Audio Visual pada Materi Menganalisis Unsur Pembangun Puisi Kelas X SMK Negeri 2 Gunungsitoli - Lilimeida Zebua; Riana (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to develop learning audio visual media on the material of analyzing the elements of poetry building class X SMK Negeri 2 Gunungsitoli. This type of research is development with the ADDIE model which consists of analysis (Analyze), design (Design), Development (Develompment), Implementation (Iplementation), Evaluation (Evaluation), the research instrument used is a validation questionnaire for material experts, linguists and design experts and a student response questionnaire. Based on the results of the study, it has been tested by material validators at revision I of 59.52%, revision II of 95.23%, language experts at revision I of 67.8% and at revision II of 100%, and design experts at revision I of 51% and revision II reached 96.7%. Furthermore, audio visuals are also very practical to use by students with a percentage of practicality in small group trials of 92.6%. And the field trial of 90% audio visual is also effective to use with the percentage of classical completeness of small group trials of 100% and field trials of 90%, From the results of the above research, the audio visual developed is feasible, practical, and effective to use in the learning process